Envelhecimento: papel da via de sinalização NRF2 sobre os mecanismos antioxidantes e anti-inflamatórios mediados pelo resveratrol - Filipe Nogueira Franco (2023)
One of the theories about aging comes from the accumulation of the generation of free radicals, in addition to a low-grade inflammatory condition. Among these molecules, Reactive Oxygen Species (ROS) and Nitrogen (RNS) stand out; in addition to pro-inflammatory cytokines such as Tumor Necrosis Factor (TNF) and Interleukin-6 (IL-6). Our body has a defense system to combat these reactive molecules, such as the enzymes Superoxide Dismutase (SOD), Catalase (CAT) and Glutathione Peroxidase (GPx). The activation of several signal transduction pathways is responsible for the efficiency of these systems. Resveratrol is a compound that has been shown to act as a potent antioxidant and anti-inflammatory. Thus, the objective was to verify whether the antioxidant and anti-inflammatory profile of resveratrol (5 µM) remains the same in leukocytes from donors of different age groups. The project was approved by the Ethics Committee (CAAE: 33842420.4.0000.5149). The individuals were divided into three groups: 20-39, 40-59 and 60-80 years old. After separation of leukocytes, assays were performed to quantify ROS and RNS. Hydrogen peroxide (150 µM) was used as a positive control. SOD, CAT, GPx, TNF, IL-6 and IL-10 were measured in commercial kits. The analysis of the antioxidant pathways PKA, AKT/PKB, AMPK, MAPK, SIRT1 and Nrf2 was carried out using specific inhibitors. Luciferase reporter gene assay and ELISA were performed to evaluate p-Nrf2 activation and expression, respectively. The analysis between age and treatment was performed using Pearson correlation (*p<0.05). The results showed that there was a reduction in ROS and RNS in leukocytes treated with resveratrol at all ages, with less effect in aging. There was an increase in CAT in leukocytes from 20-39 years old treated with resveratrol and an increase in SOD and GPx between 40-80 years old. There was a positive correlation between the antioxidant action of resveratrol on the activity and aging of the three enzymes. An antioxidant behavior of the PKA, AKT/PKB, SIRT1 and AMPK pathways was observed in leukocytes aged 20-59 years. In leukocytes from donors over 60 years of age, these pathways were silenced. The MAPK and Nrf2 pathways were active pathways at all ages, and resveratrol had an antioxidant effect on both. Nrf2 was activated in leukocytes treated with resveratrol from donors of all ages, in addition to an increase in phosphorylated protein. Resveratrol was effective in reducing TNF and IL-6 concomitantly with an increase in IL-10, with a lesser effect on aging. Dosing with the Nrf2 inhibitor proved that this pathway is also important in the anti-inflammatory context. Therefore, the Nrf2 pathway is an important biochemical mechanism responsible for the antioxidant and anti-inflammatory effects of resveratrol. This effect diminishes with aging but is still observed. The hypothesis is that Nrf2 acts (via phosphorylation by MAPK) in the transcription of genes for antioxidant enzymes and anti-inflammatory cytokines, reducing the processes of oxidative stress and chronic inflammation observed in aging.